Substance use disorders: above and beyond addiction - Kumar, Jaya (Frontiers Media SA, 2024)
Substance Use Disorder (SUD) is a mental disorder that causes an individual to compulsively consume legal or illegal drugs such as alcohol, opioids, methamphetamine, marijuana, and medications, despite harmful consequences.